Managerial activity of future physical education teachers aimed at building a positive image using visual technologies - Ryskaliyev, Sayat; Tuyakbayeva, Meruyert; Kokebayeva, Rysgul; Kazakhbayeva, Gulnur; Gabitov, Aidarbek; Kuderiev, Janibek (Frontiers in Education, 2024)
With the integration of technology and social media in education, there is increasing interest in innovative approaches to enhance managerial skills among prospective physical education and sports teachers. The integration of technology and social media into education has prompted interest in exploring innovative methods to enhance the managerial skills of prospective physical education and sports teachers. This study investigates the impact of an intervention on the managerial skills of fourth-year students majoring in Physical Culture and Sports across three educational institutions in Kazakhstan. Out of 564 participants, 355 were eligible for analysis: 167 used chatbots and 188 followed conventional classroom methods. The intervention included a 4-week team management course starting in January 2022. Chatbot users accessed various materials such as short lecture videos, stories, assignments, infographics, and audio sequences, while conventional learners attended standard lectures and practical sessions. Following the course, participants undertook a 12-week teaching practice, with chatbot users also maintaining an active Twitter presence to build a positive image as future physical education teachers. Managerial skills were assessed using a 44-item questionnaire, covering Conceptual, Human, and Technical skills. Additionally, social media popularity was measured based on Twitter activity. Results showed that both groups significantly improved their Conceptual, Human, and Technical skills after the course. Chatbot users demonstrated greater improvement in Technical skills (p = 0.003, d = 1.139), while conventional learners showed stronger Human skills (p = 0.021, d = 1.32). Specifically, the mean score for Technical skills increased from 2.71 to 3.76 for chatbot users and from 2.65 to 3.20 for conventional learners. Moreover, chatbot-aided learners further enhanced their Conceptual and Human skills through social media engagement. Correlation analysis indicated a close relationship between managerial skills and social media popularity. These findings have significant practical implications for the education and development of prospective physical education and sports teachers. Integrating chatbots and social media into educational settings offers innovative approaches to enhancing managerial skills.